Secondary vocational education and academic motivation in Sint Maarten - Kira Lee-Genzel; Semiha Bekir (Springer, 2024)
Abstract This study investigates the relationship between career and study fair participation and the motivations of Sint Maarten's secondary vocational students. Using a mixed-method design, data was collected from 98 participants (N = 98) who completed an online survey consisting of the Academic Motivation Scale (AMS). Twenty-one survey participants were subsequently interviewed. Key findings indicated that extrinsic motivation was the highest among participants. The results indicate that a single career fair alone may not be sufficient for improving the intrinsic motivation of students. Future studies should investigate the impact of attending multiple career fairs over a longer period. Overall, the research findings contribute to our understanding of academic motivation and the correlations between career and study fairs and secondary vocational student motivations in Sint Maarten. The findings highlight the importance of improving fair attendance through better promotion and logistical support for students, while also emphasizing the need to address stigmas that affect intrinsic motivation of students. The findings of this study can be particularly useful among policymakers and school leaders in the field of vocational education.